2020
DOI: 10.1002/art.41386
|View full text |Cite
|
Sign up to set email alerts
|

Fcγ Receptor I–Coupled Signaling in Peripheral Nociceptors Mediates Joint Pain in a Rat Model of Rheumatoid Arthritis

Abstract: Objective. Rheumatoid arthritis (RA) is often accompanied by joint pain and inflammation. Previous studies have demonstrated that functional Fcγ receptor I (FcγRI) is expressed in dorsal root ganglion (DRG) neurons and might contribute to pain in rodent models of antigen-induced arthritis (AIA). This study was undertaken to elucidate the roles of nociceptive neuronal FcγRI-coupled signaling in the development of joint pain in AIA. Methods. RNA sequencing was used to investigate the transcriptome profile change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Our previous work has demonstrated the contribution of FcγRI to arthritis pain in several murine models of inflammatory arthritis ( 14 , 16 ). We and other groups have reported that FcγRI is also present in primary sensory neurons besides immune cells ( 13 , 24 , 25 ). Moreover, we showed that neuronally expressed FcγRI mediated the sensitization of joint nociceptors and arthritis pain during inflammation in animal models of RA through a mechanism independent of inflammation ( 14 ).…”
Section: Discussionmentioning
confidence: 68%
“…Our previous work has demonstrated the contribution of FcγRI to arthritis pain in several murine models of inflammatory arthritis ( 14 , 16 ). We and other groups have reported that FcγRI is also present in primary sensory neurons besides immune cells ( 13 , 24 , 25 ). Moreover, we showed that neuronally expressed FcγRI mediated the sensitization of joint nociceptors and arthritis pain during inflammation in animal models of RA through a mechanism independent of inflammation ( 14 ).…”
Section: Discussionmentioning
confidence: 68%
“…In addition to immune cells, we and other groups have identified that FcγRI is also expressed in primary sensory neurons 25,26,44,45 . Moreover, our recent study showed that neuronally expressed FcγRI mediated hyperactivity of joint sensory neurons and arthrits pain in animal models of RA through a mechanism independent of inflammation 26 .…”
Section: Discussionmentioning
confidence: 95%
“…Hence, IgG-IC accumulation in the inflamed joint is sufficient to directly stimulate and sensitize joint sensory neurons through neuronal FcγRI, resulting in joint pain. Direct FcγRI blockade with neutralizing antibodies and FcγRI genetic knockout substantially reduced pain-related behaviors in the AIA mouse model [75,76]. These findings suggest that FcγRI can contribute to arthritis pain through a non-inflammatory mechanism, making it a promising therapeutic target in RA patients with pain refractory to current anti-inflammatory treatments (Figure 3.6).…”
Section: Neuropathy and Painmentioning
confidence: 89%
“…IgG-IC/FcγRI signaling has been linked to both the pathogenesis [54,73,81] and disease-associated pain [8,75,76] in RA. Joint pain is a prominent clinical characteristic of RA, which is caused in part by synovitis and joint destruction [94].…”
Section: Neuropathy and Painmentioning
confidence: 99%
See 1 more Smart Citation